“Out” Or “Not Out” in Higher Education: The Lived Experiences of a Transgender Student - Hensman, G.H.; Dilogini, S. (University of Jaffna, 2022)
Creating transgender awareness in higher education institutions and guiding University student counsellors is very much needed. Focusing on this, this study seeks insights into the general perspective of the lives, experiences and vulnerabilities of female-to-male transgender people. There has been very little research explored on the lived experiences of transgender students in higher education in teaching and learning environment, Sri Lanka. To fill this gap, current study provides an in-depth understanding of transgender student’s anxieties that regulates the perceptions of others in accordance with transgender people. Comprehensive lived experiences have been collected through trans’ own experiences. Using Interpretative Phenomenological Analysis (IPA), the respondent shared his eight years buried life experiences with the researchers. The following insights were generated through researchers’ interpretation such as; seeking a secured environment, start to educate yourself about transgender, choose to behave mentally or physically, I was born but when will I live?. These themes suggest gender identity, and particularly trans identities and experiences in higher education curricula. Findings revealed that the education and training should be given to students, academics and others to help them better understand gender varieties. Thus, this study provides deeper understanding and awareness regarding the vulnerability of transgender students in higher education and how to create a safe environment to transgender people.
Keywords: Female-to-male; Gender identity; Higher education; Interpretative phenomenological analysis; Transgender